THE PERSUASION OF TELEVISION ADVERTISEMENTS FOR CHILDREN - Dr. Ismail Khalil Ismail, Yousif Munqith Hamdi, Dr. Safaa Hassan Hussein (PalArch's Journal of Archaeology of Egypt / Egyptology, 2021)
Television advertisements are distinguished from other television arts in that they are works that rely on reduction in advertising content, which leads to the employment of graphic and audio components with clear connotations that are easily communicated in a way that ensures achieving persuasion about what is presented to them (children) of meanings characterized by aesthetic values ??that enhance the convictions of the recipient In tension and attraction to what is seen in the events and advertising contents. The levels of the recipients vary and vary, and it is at the same time imposing the responsibility of the advertiser to address the minds of the movers, regardless of their different awareness, cultures and behavior, which is directly related to the age of the recipient and his environment. Several, such as decoration, costumes, colors and lighting, which leave a direct impact on the recipient, and the children remain as an important segment of the recipients in privacy when addressing them in form and voice in order to achieve persuasion of what is presented to them of advertising content that achieves persuasion through their suspense and motivation towards the implementation of the advertising messages to be achieved and in order to achieve the desired goals related to deliver The guiding and indicative contents through television advertisements and the possibility of achieving these goals by convincing children in a smooth and unpromising manner.